Reading Trauma and Reading History: An Analysis of Nepali Post-Conflict Narratives - Pokharel, Badri Prasad (Interdisciplinary Journal of Management and Social Sciences, 2025)
This article tries to navigate some important works written during or after the ten year-long Maoist insurgency that happened in Nepal from 1995 to 2005 causing the death toll of more than seventeen thousand people, that illuminate the pathetic aspect of the then Nepali society gripped on the edge of a sword, hence suffering from trauma – even not able to narrate what stroke they were going through. To bring out the historical facts of the decades-long conflict, some notable trauma theorists and their excerpts have been applied. Among the various works written during and after the insurgency, fourteen works written about the conflict have been analyzed from the traumatic perspectives illuminating the painful life of the people who were badly affected by the consequences of the war between the security forces and the insurgents. The ten-year long Moist insurgency, though seen from the negative point of view assessing the losses and agony, has brought some exemplary assumptions for creative minds by presenting their experiences in the written form – narratives.